COMPARISON OF INTERCULTURAL COMMUNICATIVE COMPETENCE REALIZATION IN CAMBRIDGE CHECKPOINT ENGLISH 7 AND BRIGHT AN ENGLISH 1 - Maria Kartika Primaquinna Sejati; Zulfa Sakhiyya (Universitas Negeri Semarang, 2025)
This research investigates the intercultural communicative competence of EFL textbooks. Intercultural communicative competence is crucial for learners to gain cultural awareness and avoid misunderstandings given diverse cultural background. This objective is achieved by comparing and evaluating the intercultural communicative competence in the learning materials of Cambridge Checkpoint English 7 and Bright an English 1. There are three reasons why this research emphasizes textbooks. First, textbooks hold an integral role in teaching and learning activities. Textbooks becomes the main resource for both teachers and students on how the lesson should be taught. Second, the textbook gives a variety of cultural information. Third, the representation of the cultural contents might cover the target culture and also international culture. The research employed a content analysis approach and was qualitatively interpreted. The data used in this research are the learning materials in the form of reading texts, short dialogues, images, words, and sentences related to cultural content. The data are collected through document review to note down the cultural content in the learning materials from both of the English textbooks. The findings reveal that both of the textbooks integrate diverse cultural content. Cambridge Checkpoint English 7 selectively incorporates ICC dimensions, emphasizing knowledge, skills of discovery, and interaction, while there is no evidence of attitude and cultural awareness dimensions. In contrast, Bright an English 1 only emphasize on knowledge dimension. These findings point to the textbooks' shortcomings in developing thorough intercultural communication ability. In order to better prepare students for intercultural understanding and communication in a globalized environment, this study emphasizes the necessity for more comprehensive and balanced ICC integration in educational materials.